(untitled) (Kriminalističke teme, 2004)
Movement and useing of NCB resources by terrorists is truthly taking very highe place on list of danger for all the countries in the world today. This paper is focused to siginificance of prevention, but first of all to limitation of terrorists access to NCB resources, as one of the most importante factor of prevention of NCB terrorism, and neccessity to undertake all prevention actions in domain of Civil protection, as one of consisted element of security of each country. The deterimant role is placed to security policy in this movement on micro and macro planes.